The Correlation Between Learning Sufism Moral And Spiritual Intelligence Of Prospective English Language Teachers In Islamic English Education Study Program - Yasmine Mumtaazah; Zaitun Qamariah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the relationship between learning Sufism morals (akhlak Sufism) and the spiritual intelligence of prospective English teachers. This literature review integrates the concept of Sufism morals, which emphasizes the formation of moral and spiritual character, with spiritual intelligence which is considered important in the teaching profession. This study found that learning Sufism morals can increase the spiritual awareness and professional ethics of prospective English teachers. High spiritual intelligence helps teachers face emotional and ethical challenges in teaching and supports the creation of a harmonious and inspiring learning environment. The results of this study indicate that the integration of Sufism morals learning in the English education curriculum can be an effective strategy for improving the quality of education and teacher character. It is hoped that prospective teachers who have strong spiritual intelligence can be good role models for their students, and contribute to the formation of a moral and noble generation.